Dibutyl phthalate-induced activation of ROS and ERK1/2 causes hepatic and renal damage in Kunming mice. (August 2019) - Cheng, L; Li, J; Cheng, J; Wu, Z
Dibutyl phthalate (DBP), a ubiquitous environmental contaminant, has been reported to be involved in hepatic and renal tissue damage. However, the role of DBP in oxidative stress and in extracellular signal-regulated kinase (ERK1/2) pathways remains unclear. To investigate the underlying mechanism, Kunming (KM) mice received daily doses of combinations of 50 mg/kg DBP, 50 mg/kg vitamin E (VitE), and 1 mg/kg PD98059 for 28 consecutive days. Any changes in reactive oxygen species (ROS) and malondialdehyde (MDA) levels, as well as any histopathological alterations in tissues, were observed to assess oxidative stress. In addition, the levels of alanine aminotransferase, aspartate aminotransferase, and albumin in serum were used to evaluate liver function. The levels of creatinine and urea nitrogen in serum were measured to evaluate kidney function. We found that DBP significantly increased oxidative damage and the expression of phosphorylated ERK1/2. Furthermore, pretreatment with the ERK inhibitor PD98059 followed by the antioxidant VitE attenuated the levels of ROS, MDA, ERK1/2 phosphorylation, and DBP-mediated disorders, indicating that the oxidative stress and the ERK1/2 pathways are associated with DBP-induced hepatic and renal dysfunction in KM mice.